2020
DOI: 10.3889/oamjms.2020.3233
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Capute Scores with CD4 Count among Human Immunodeficiency Virus-infected Children in Sanglah Hospital, Bali, Indonesia

Abstract: BACKGROUND: Cognitive, motoric, and language development in a human immunodeficiency virus (HIV)-infected child is an important issue that affects developmental milestone and quality of life. The effect of HIV infection on cognitive function must be detected early to prevent delayed cognitive, motoric, and language function. AIM: This study aimed to assess the correlation of cognitive scores with CD4 count among HIV-infected children in pediatrics polyclinic Sanglah Hospital, Bali. METHODS: This cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…18 Another study by Supadma et al, 2020 also stated that there was a relationship between CD4 levels and Capute Scale values in HIV-infected children compared to children who were not infected with HIV. 19 Research by Ravindran et al, 2014 found that children with HIV tend to suffer cognitive deficits in the domains of attention, language, verbal learning and memory, visuomotor functions, fine motor performance, and executive functions. 17,20 Research by Cohen et al, 2015, stated that the cognitive performance of HIVinfected children is poor compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study by Supadma et al, 2020 also stated that there was a relationship between CD4 levels and Capute Scale values in HIV-infected children compared to children who were not infected with HIV. 19 Research by Ravindran et al, 2014 found that children with HIV tend to suffer cognitive deficits in the domains of attention, language, verbal learning and memory, visuomotor functions, fine motor performance, and executive functions. 17,20 Research by Cohen et al, 2015, stated that the cognitive performance of HIVinfected children is poor compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%